education in values, an approach to strategies as a way for the collective construction of knowledge (Revista Electrónica REDINE, 2019)
The purpose of this research was to reveal the theoretical-practical meanings that the teachers   of the University Centroccidental "Lisandro Alvarado" (UCLA) give to education in values. In the study I used as input assumptions the formative models on education in values and teaching practice. I did the methodological  from the qualitative approach, using ethnography as a research method, with the support of the techniques: participant observation and in-depth interviews. The selection of key informants was made intentionally considering their experience in the subject and of access to their subjectivity. The information gathered from the interviews and observations was recorded and organized in matrices. With the use of hermeneutics, I interpreted, reflected and reorganized, thus emerging the category Meanings built about university teaching and as a sub category various strategies as a way for the collective construction of knowledge. Among the most important findings I obtained, that these teachers promote the pedagogy of understanding, that is, contextualize the contents and use strategies for the collective construction of knowledge such as: group discussions in the classroom, expository type, such as lectures or the exhibitions by the students, the construction and elaboration, such as the ethnographies in classes and the relational or dynamic that seek to catch the attention of students through motivation, such as videos, songs, jokes, and other much deeper like anecdotes, the use of fables to interpret or read text and poetry books.